The transition urban planning history of Lisbon Metropolitan Area - Marat-Mendes, T. (2019)
Drawing from an ongoing research project 'SPLACH - Spatial Planning for Change, which aims to inform a sustainable planning transition of Portuguese metropolitan areas, this presentation identifies the planning paradigms which have guided the urban planning of Lisbon, its region and metropolitan area, during twentieth century. The influence of specific theories such as the Garden City (1898-1902), the Chartre d'Athénes (1933-1943), the Doorn Manifesto (1954) and the Compact City (1997) on strategic planning documents inclunding the 'Plano Director de Urbanização de Lisboa' (1938-1948), the 'Plano Director Municipal de Lisboa' (1954-1958), and the municipal and regional masterplans established after the 1974 Portuguese Democratic revolution are here identified. Such analysis is constructed through an overview of municipal and subregional plans and of neighbourhoods created in them, which allows an analysis of the metabolic and morphological transitions which have marked twentieth century Lisbon Metropolitan Area (LMA) urban planning history. By doing so, we seek to establish which were the impacts of these transitions, inclunding on urban form, how have these changed the role of urban growth in LMA and how to interpret and optimize such built heritage today, when Sustainability urges for change.